Effect of Donor Tumor Necrosis Factor-alpha and Interleukin-10 Genotypes on Delayed Graft Function and Acute Rejection in Kidney Transplantation (Iranian Journal of Kidney Diseases, 2013)
Introduction. This study evaluated the influence of interleukin-10 (IL10) gene -1082G>A and tumor necrosis factor-alpha (TNF) gene -308G>A polymorphisms in the donor and recipients on the acute rejection (AR) episodes and delayed graft function (DGF) in kidney transplant recipients. Materials and Methods. The IL10 -1082G>A and TNF -308G>A polymorphisms were determined in 100 kidney allograft recipients and their donors using the polymerase chain reaction-amplification refractory mutation system polymerase chain reaction-restriction fragment length polymorphism methods. Transplantation outcomes were determined in terms of AR and DGF criteria. Results. The A allele of the TNF polymorphism (high producer) in the donors was associated with DGF in the recipients (odd ratio, 3.1; 95% confidence interval, 1.2 to 8.1). There was also a significant association between the combination of donor's IL10-TNF genotypes and DGF (odd ratio, 4.8; 95% confidence interval, 1.4 to 17.1); the frequency of a combination of IL10 AA or GA and TNF AA or GA was higher in the recipients with DGF. No association was found between the donors and recipients' IL10 -1082G>A and TNF -308G>A polymorphisms and AR. No association was detected between recipients and donors' IL10 polymorphisms or recipients' TNF polymorphisms and DGF. Conclusions. This study showed that donors with high TNF production may have increased risk of DGF in their recipients. Routine screening of these gene polymorphisms may have a clinical role in identifying patients at risk of DGF.